Transparent ceramic coating as well as preparation method and application thereof in small household appliances

By using transparent ceramic coatings on small appliances, combined with sandblasting and nitriding treatment, the problem of ceramic coatings sag on small appliances such as air fryers is solved, achieving high pass rate and excellent non-stickness, satisfying the appearance of fluorine coatings and performance requirements.

CN119264707APending Publication Date: 2025-01-07ZHEJIANG LI PORCELAIN NEW MATERIAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411446322.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing ceramic coatings are prone to sag when spraying small household appliances such as air fryers, and cannot meet the requirements of finished product qualification and non-stickness of fluorine coatings. Especially on substrates with pores and holes, the dry film thickness is insufficient and cannot be achieved. Excellent hiding and non-stick properties.

Method used

Transparent ceramic coating is divided into two layers: primer and topcoat. After sandblasting and nitriding, spraying at room temperature. The composition of primer and topcoat includes silicon sol, silane, hydroxyethyl cellulose aqueous solution, and organic titanium intersecting. Coupling agents, etc., control the dry film thickness between 14-20μm to ensure non-stickness and appearance comply with fluorine coating standards.

Benefits of technology

It has achieved direct spraying at room temperature without sagging, paint does not accumulate in holes, the product pass rate is greatly increased to more than 96%, and its appearance and non-stickness meet the standards of fluorine coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264707A_ABST
    Figure CN119264707A_ABST
Patent Text Reader

Abstract

The invention discloses a transparent ceramic coating as well as a preparation method and application thereof in small household appliances. The coating is divided into a primer layer and a finish layer which are colorless and transparent, and the primer contains silica sol, silane, a 5wt% hydroxyethyl cellulose aqueous solution, formic acid, a flatting agent, isopropanol, an organic titanium cross-linking agent and the balance deionized water; compared with the primer, the finish paint is also added with a non-stick auxiliary agent and an emulsifier. According to the transparent ceramic coating provided by the invention, through cooperation of a construction process, the transparent ceramic coating is applied to the surface of a base material with pores and holes, such as a frying basket of an air fryer, so that the color and the appearance of a fluorine coating are achieved, the thickness of a dry film is 15-20 microns, and the transparent ceramic coating has excellent non-stickiness; the coating is directly sprayed at normal temperature without sagging, the coating cannot be accumulated in pores, and the qualified rate of finished products is greatly improved and can reach 96% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic coatings, and in particular relates to a transparent ceramic coating and a preparation method thereof and application thereof in small household appliances. Background Art

[0002] The basket of an air fryer is usually sprayed with fluorine coating, which is easy to apply and has excellent non-stick properties. However, since fluorine coating is a PFAS substance, PFAS substances have strong stability and bioaccumulation, which makes it difficult to decompose in nature and difficult to be excreted from the human body, causing certain harm to the environment and human health. Therefore, various countries have successively issued regulations to restrict the use of PFAS. As the time for the implementation of the PFAS regulations approaches, the use of fluorine coatings will also be restricted. Therefore, it is necessary to find a coating to replace fluorine coatings. Since fluorine coatings have been widely used in the cookware and small appliance industries in the past few decades, the appearance and color of fluorine coatings can be said to be deeply rooted in the hearts of the people and are generally loved by merchants and consumers. Therefore, the substitute for fluorine coatings needs to meet the following conditions: (1) The coating has the characteristics of safety, health and environmental protection, and has excellent non-stick properties; (2) The appearance and color are similar to those of fluorine coatings; (3) The same spraying construction method as fluorine coatings, that is, spraying directly on the substrate at room temperature.

[0003] Ceramic coatings are considered to be the first choice for replacing fluorine coatings. Ceramic coatings are safe, healthy and environmentally friendly, and have excellent non-stick properties. They have been widely used in the cookware industry in recent years. They can achieve colors and appearances similar to those of fluorine coatings by toning. However, the spraying construction process of ceramic coatings is cumbersome and complicated compared to fluorine coatings. To achieve a full appearance, good hiding power and excellent non-stick properties, the dry film thickness of ceramic coatings needs to reach 28-40μm. The solid content of ordinary ceramic coatings is about 50-55%, and the wet film thickness needs to reach 50-80μm during spraying. If the process of direct spraying at room temperature is adopted, due to the low viscosity of ceramic coatings, it is easy to produce sagging during spraying. There are many gaps and small round holes on the sides and bottom gaskets of the air frying basket. The sagging paint will accumulate around the gaps and holes, so the qualified rate of finished products can only reach 50-60%. In order to avoid the sagging phenomenon of ceramic coatings, the substrate needs to be preheated to 45-55℃ before spraying, and then spraying. This spraying construction process of ceramic coatings cannot meet the requirements of replacing fluorine coatings.

[0004] Although ceramic coatings that can be sprayed at room temperature have been developed, this type of spraying is based on a flat substrate without pores and holes. For substrates with structures such as air fryer baskets, in order to prevent the coating from accumulating around the pores and holes, the dry film thickness after spraying can only be below 20μm. For ordinary ceramic coatings, this thickness cannot meet the requirements of actual use in terms of appearance, hiding power and non-stickiness. Summary of the invention

[0005] In view of the above-mentioned problem of replacing fluorine coating with ceramic coating, the purpose of the present invention is to provide a transparent ceramic coating and its preparation method and application in small household appliances. The transparent ceramic coating provided by the present invention is applied to the surface of a substrate with pores and holes, such as an air fryer basket, through the coordination of the construction process, to achieve the color and appearance of the fluorine coating, the dry film thickness is between 14-20μm, and it has excellent non-stickiness. It will not sag when sprayed directly at room temperature, and the coating will not accumulate in the pores and holes. The qualified rate of finished products is greatly improved, which can reach more than 96%.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] <First aspect>

[0008] The present invention provides a transparent ceramic coating, which is divided into two layers, a primer and a topcoat, both of which are colorless and transparent, wherein the primer is 100% and is composed of: silica sol: 42-45%, silane: 30-32%, 5wt% hydroxyethyl cellulose aqueous solution: 4-5%, formic acid: 0.7-1.0%, leveling agent: 0.5-1%, isopropanol: 8-10%, organic titanium cross-linking agent: 3-4%, and deionized water: the balance;

[0009] The topcoat is composed of 100% silica sol: 36-38%, silane: 36-38%, formic acid: 0.7-1%, leveling agent: 1-1.5%, non-stick agent: 5-6%, emulsifier: 0.5-1%, isopropyl alcohol: 8-10%, organic titanium cross-linking agent: 1-2%, and deionized water: the balance.

[0010] As an embodiment, the transparent ceramic coating is applied to the surface of a workpiece after sandblasting or shot blasting, and nitriding treatment.

[0011] As an embodiment, the silica sol is selected from Bindzil 2034DI of Akzo Nobel, ST-O-40 of Nissan Chemical, HS-40, etc.

[0012] As an embodiment, the silane is selected from a combination of methyltrimethoxysilane and methyltriethoxysilane in a mass ratio of 3:1 to 4:1.

[0013] As an embodiment, the leveling agent is selected from at least one of BYK-333 and Dow Corning DC-57.

[0014] As an embodiment, the organic titanium crosslinking agent is selected from DuPont TM 371.

[0015] As an embodiment, in the topcoat or primer, the weight ratio of isopropyl alcohol to the organic titanium crosslinking agent is 1:1-1.5:1.

[0016] As an embodiment, the non-stick agent is a non-stick agent having a hydroxyl group at the end of the molecular chain.

[0017] As an embodiment, the emulsifier is a cationic emulsifier.

[0018] As an embodiment, the emulsifier is a cationic emulsifier with an organic quaternary ammonium salt structure.

[0019] As an embodiment, the emulsifier is selected from hexadecyltrimethylammonium bromide, octadecyldimethylbenzylquaternary ammonium chloride, benzalkonium chloride, and benzalkonium bromide.

[0020] <Second Aspect>

[0021] The present invention also provides a method for applying the aforementioned transparent ceramic coating in small kitchen appliances, the method comprising sandblasting or shot blasting, nitriding the workpiece, spraying a transparent ceramic primer, spraying a transparent ceramic topcoat and then curing.

[0022] As an embodiment, after the workpiece is sandblasted or shot blasted, the surface roughness of the workpiece reaches 3-5 μm.

[0023] As an implementation scheme, the sandblasting: using compressed air as the power, using 60-80 mesh white corundum or brown corundum sand, and spraying it at high speed onto the surface of the workpiece to be processed, and the surface roughness of the workpiece after sandblasting reaches 3-5 μm.

[0024] As an embodiment, the treatment temperature of the nitriding treatment is 550-570° C., the pressure of the nitriding furnace is controlled at 11-13 kPa, and the nitriding time is 2-3 hr.

[0025] In some implementation examples, a nitriding furnace is used to heat the workpiece to 550-570° C., ammonia and nitrogen are injected, the furnace pressure is controlled at 11-13 kPa, the nitriding time is 2-3 hours, and the workpiece is taken out after natural cooling.

[0026] As an embodiment, the spray transparent primer is prepared by mixing the primer composition 1 (i.e., the organic titanium crosslinking agent and isopropyl alcohol are mixed in a weight ratio of 1:1-1.5:1) and the primer composition 2 (the remaining components are mixed) stored separately during the preparation of the primer and then immediately applied, specifically spraying at room temperature, and the dry film thickness of the primer is about 6-8 μm. In some embodiments, the wet film thickness of the primer is 15-20 μm, and the solid content of the transparent primer is about 40%.

[0027] As an embodiment, the spraying transparent topcoat is to mix the topcoat composition 1 (i.e., the organic titanium crosslinking agent and isopropyl alcohol are mixed in a weight ratio of 1:1-1.5:1) and the topcoat composition 2 (the remaining components are mixed) which are stored separately during the preparation of the topcoat and then immediately apply the topcoat, specifically, after spraying the primer, spray the topcoat in a wet-on-wet manner, and the dry film thickness of the transparent topcoat is 8-12 μm. In some embodiments, the wet film thickness of the topcoat is 20-30 μm, and the solid content of the topcoat is about 40%.

[0028] As an embodiment, the curing process is: 80-100°C, 3-5 min; 200-260°C, 8-10 min.

[0029] As an embodiment, the workpiece is a component for a small kitchen appliance, such as an air fryer basket, a microwave oven, an interior panel of an oven, etc.

[0030] <Third Aspect>

[0031] The present invention also provides a method for preparing the aforementioned transparent ceramic coating, the method comprising the following steps:

[0032] A. Preparation of primer:

[0033] A1, mixing the organic titanium crosslinking agent and isopropanol in a weight ratio of 1:1-1.5:1, and setting aside for use, which is recorded as primer 1;

[0034] A2, adding silica sol to 5wt% hydroxyethyl cellulose aqueous solution and mixing evenly;

[0035] A3, silane, formic acid, leveling agent, deionized water, and the remaining isopropanol are mixed evenly, and then the solution of step A2 is added, and the mixture is placed on a roller frame, and rolled at 120-150 rpm for 12-14 hours to obtain a transparent ceramic primer 2;

[0036] B. Preparation of topcoat:

[0037] B1, mixing the organic titanium crosslinking agent and isopropanol in a weight ratio of 1:1-1.5:1, and setting aside for use, which is recorded as topcoat 1;

[0038] B2. Evenly mix silane, formic acid, leveling agent, non-stick additive, emulsifier, deionized water and the remaining isopropanol, then add silica sol, place on a roller stand, roll at 120-150 rpm for 12-14 hours to obtain ceramic topcoat 2, and the tested pH is 4.0-5.2.

[0039] The transparent ceramic primer 2 has a pH of 4.0-5.2 and a viscosity of 12-15s after applying 4 cups of paint.

[0040] The pH of the ceramic topcoat 2 is 4.0-5.2.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] (1) By sandblasting, nitriding and spraying transparent ceramic coating on the surface of the workpiece, the color and appearance similar to fluorine coating are achieved;

[0043] (2) By controlling the thickness of the ceramic coating primer and topcoat, the total thickness is controlled at ≤20μm, so that the coating does not sag during spraying at room temperature and does not accumulate in the holes and gaps of the workpiece. The qualified rate of sprayed finished products has increased from 60% to more than 96%;

[0044] (3) By adding an organic titanium crosslinker to the topcoat, the organic titanium crosslinker can undergo a crosslinking reaction with the -OH remaining on the surface of the ceramic coating, significantly reducing the amount of residual -OH. Therefore, the water resistance and non-stick durability of the ceramic coating can be improved. Compared with ordinary ceramic coatings, the non-stick property has been greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0046] Figure 1 This is a comparison chart of the workpiece before and after spraying transparent ceramic coating; the left side shows the color of the workpiece after sandblasting and nitriding, before spraying transparent ceramic coating (black gray); the right side shows the color of the workpiece after sandblasting and nitriding, after spraying transparent ceramic coating, which is similar to the color of fluorocarbon coating. DETAILED DESCRIPTION

[0047] The present invention is further illustrated by the following examples, but any example or combination thereof should not be construed as limiting the scope or implementation of the present invention. Without departing from the spirit and scope of the present invention, those skilled in the art may make any modifications or changes to the technical solution of the present invention, and such modifications and changes are also included in the scope of the present invention.

[0048] In the examples, if the specific conditions are not specified, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for all reagents or instruments, they are all conventional products that can be purchased commercially. In order to better illustrate the present invention, numerous specific details are provided in the specific embodiments below. It should be understood by those skilled in the art that the present invention can be implemented equally without certain specific details. In other embodiments, methods, means, equipment and steps well known to those skilled in the art are not described in detail to highlight the gist of the present invention.

[0049] The transparent ceramic coating of the present invention is divided into two layers, a primer and a topcoat, both of which are colorless and transparent. The primer is 100% and has the following composition:

[0050] Silica sol: 42-45%,

[0051] Silane: 30-32%,

[0052] 5wt% hydroxyethyl cellulose aqueous solution: 4-5%,

[0053] Formic acid: 0.7-1.0%,

[0054] Leveling agent: 0.5-1%,

[0055] Isopropyl alcohol: 8-10%,

[0056] Organic titanium crosslinker: 3-4%,

[0057] Deionized water: balance.

[0058] in:

[0059] Silica sol: The main film-forming substance of ceramic coatings, rich in -OH on the surface, is a common commercial product, such as Bindzil 2034DI from Akzo Nobel, ST-O-40 from Nissan Chemical, and Grace HS-40, etc.

[0060] Silane: auxiliary film-forming substance, among which methyltrimethoxysilane:methyltriethoxysilane=3:1~4:1. On the one hand, the hydrolysis and polymerization speed of methyltrimethoxysilane is fast, while the hydrolysis speed of methyltriethoxysilane is slow. Mixing the two can prolong the hydrolysis and polymerization time, so that the sol-gel reaction of the ceramic coating can be fully carried out, and the formed coating has a large cross-linking density, good density, and excellent wear resistance and non-stickiness. On the other hand, both silanes are trifunctional groups, Si is connected to three -OCH3, and three silanol groups (Si-OH) are formed after hydrolysis. After polymerization with silica sol, a coating with a three-dimensional cross-linked structure can be formed. The structure of the coating is compact and not easy to crack.

[0061] 5wt% hydroxyethyl cellulose aqueous solution: a relatively mild water-based paint thickener, with a small viscosity change in the pH range of 2-12, which can adjust the viscosity of ceramic paints, has very good transparency, has better leveling properties than other types of cellulose, and is rich in -OH on the molecular chain surface, which can undergo cross-linking reactions with organic titanium cross-linking agents. Since common silica sols are acidic and alkaline, finished ceramic paints are acidic (4.0-5.2), and the pH value varies greatly. If other types of cellulose are used as thickeners, the pH change will cause a large change in the viscosity of the paint, making it impossible to apply. In addition, hydroxyethyl cellulose has better leveling properties than other types of cellulose. If other types of cellulose are used, the paint film will have poor leveling properties after spraying, and the coating will have low gloss.

[0062] Formic acid: a catalyst for the sol-gel reaction of ceramic coatings. The pH value of ceramic coatings after reaction is adjusted to between 4.0 and 5.2. Methyltrimethoxysilane undergoes polycondensation reaction with silica sol after hydrolysis under acidic conditions to generate ceramic coatings. Since there is methyltriethoxysilane in the formula, formic acid is used as a catalyzer. Due to the strong acidity and high catalytic efficiency of formic acid, the hydrolysis rate of methyltriethoxysilane can be accelerated. Due to the different acidity and catalytic efficiency of different acids, if other acids such as acetic acid, citric acid, benzoic acid, and hydrochloric acid are used to replace the acid in this formula, the pH value of the ceramic coating after aging will not be within the control range. If the pH value is less than 4.0, on the one hand, the ceramic coating can be used for a very short time, usually less than 12 hours, and the paint film will dry; on the other hand, the crosslinking reaction speed of the organic titanium crosslinker is too fast, the paint film is not leveled well, and the coating has low gloss. If the pH value is >5.2, the silica sol in the ceramic coating is prone to gelation and precipitation, resulting in deterioration of the coating.

[0063] Leveling agent: It helps the coating to form a flat, smooth and uniform coating during the drying process. For example: BYK-333, Dow Corning DC-57.

[0064] Organic titanium crosslinker: It is an environmentally friendly water-based coating crosslinker and adhesion promoter. It can react with various types of resins containing -OH and -COOH to improve the crosslinking density of the water-based system, improve adhesion, water resistance and other functions. For example: DuPont TM 371, etc. It can be stably stored in aqueous solution with pH value = 7-8. When pH value < 6 or pH value > 8 or temperature > 100°C, 371 will undergo a cross-linking reaction, and the reaction rate changes with changes in pH or temperature.

[0065] In ceramic coating system, the main film-forming substance - silica sol has a rich -OH on its surface, and the auxiliary film-forming substances methyltrimethoxysilane and methyltriethoxysilane form silanol (-SiOH) after acidic hydrolysis. In addition, the thickener hydroxyethyl cellulose molecular chain is also rich in -OH, so the organic titanium cross-linking agent can fully cross-link with the ceramic coating system to play a role.

[0066] Isopropyl alcohol: an organic solvent, used as a special wetting agent for organic titanium crosslinkers, mixed with organic titanium crosslinkers at a ratio of 1:1-1.5:1 to improve compatibility with water-based coatings.

[0067] The topcoat is calculated as 100%, and its composition is as follows:

[0068] Silica sol: 36-38%,

[0069] Silane: 36-38%,

[0070] Formic acid: 0.7-1%,

[0071] Leveling agent: 1-1.5%,

[0072] Non-stick additive: 5-6%,

[0073] Emulsifier: 0.5-1%,

[0074] Isopropyl alcohol: 8-10%,

[0075] Organic titanium crosslinker: 1-2%,

[0076] Deionized water: balance.

[0077] Among them, silane: methyltrimethoxysilane: methyltriethoxysilane = 3:1 to 4:1.

[0078] Non-stick additives: To improve the feel and non-stick properties of the coating, non-stick additives with hydroxyl groups at the end of the molecular chain are preferred. They can participate in the reaction during the maturation of the ceramic coating and connect to the molecular chain in the form of chemical bonds, which can provide the ceramic coating with more lasting non-stick properties. Common commercial products, such as 3600 from Guangzhou Hanju Polymer Materials Co., Ltd. and K-766 from Guangdong Biaomei Fluorosilicone New Materials Co., Ltd.

[0079] Emulsifier: Cationic emulsifiers are used, which can be stable under weak acidic conditions. For example, emulsifiers with organic quaternary ammonium salt structures such as hexadecyltrimethyl quaternary ammonium bromide, octadecyldimethylbenzyl quaternary ammonium chloride, benzalkonium chloride, benzalkonium bromide, etc. The amount of non-stick additive added to the topcoat is relatively large. Adding emulsifiers is beneficial to improve the compatibility of non-stick additives and topcoat, which can not only increase the non-stick durability of the coating, but also reduce the floating oil on the coating surface. If no emulsifier is added, there will be obvious floating oil on the surface after the paint film is cured.

[0080] Organic titanium cross-linking agent: isopropyl alcohol = 1:1-1.5:1 (weight ratio), which can undergo a cross-linking reaction with the -OH remaining on the molecular chain of the ceramic coating, thereby improving the water resistance and non-stick durability of the coating.

[0081] The preparation steps of the primer are as follows:

[0082] (1) Mixing an organic titanium crosslinking agent and isopropanol in a weight ratio of 1:1-1.5:1 and setting aside; the organic titanium crosslinking agent and isopropanol can improve the compatibility and stability with the water-based coating system. If the organic titanium crosslinking agent is directly added to the water-based coating, the coating will be delaminated, the crosslinking reaction will be insufficient, the curing speed of the coating will be slow, the adhesion will be slightly poor, and the water resistance will be poor;

[0083] (2) Preparation of 5 wt% hydroxyethyl cellulose aqueous solution: 95 g of deionized water and 5 g of hydroxyethyl cellulose can be weighed, first the deionized water is heated to above 35°C, and hydroxyethyl cellulose is gradually added under stirring until it becomes a uniform transparent solution, and then it is set aside. The solubility of hydroxyethyl cellulose in cold water is not high (<5 wt%) and it dissolves slowly, but the solubility of hydroxyethyl cellulose can be significantly improved in hot water, and it becomes a colorless transparent solution after complete dissolution.

[0084] (3) Add the formulated amount of silica sol to the 5 wt% hydroxyethyl cellulose aqueous solution while stirring, mix well and set aside. The viscosity of hydroxyethyl cellulose changes little and is stable when the pH value is within the range of 2-12.

[0085] (4) Silane, formic acid, leveling agent, deionized water, and the remaining isopropanol are mixed evenly, and then the solution of step (3) is added, and the mixture is placed on a roller frame and rolled at 120-150 rpm for 12-14 hours to obtain a transparent ceramic primer having a pH of 4.0-5.2 and a coating viscosity of 12-15s for 4 cups;

[0086] After the ceramic coating is matured, the pH is controlled at 4.0-5.2, which can ensure that the coating can be used for 72 hours and the coating performance is excellent; if the pH is less than 4.0, the coating can be used for a very short time, generally less than 12 hours; if the pH is greater than 5.2, the silica sol is prone to gelation and failure, which also leads to a short shelf life of the coating, generally less than 12 hours.

[0087] The viscosity of the primer should be controlled within 12-15s. If the viscosity is too low, the film thickness will be too thin, resulting in poor non-stick durability of the coating. If the viscosity is too high, the coating leveling will be poor, the coating appearance will be poor and the gloss will be low, and it will easily clog the spray gun, affecting construction efficiency.

[0088] The solution of step (1) needs to be stored separately and applied immediately after being mixed evenly with the primer before construction. Organic titanium crosslinking agent is a fast crosslinking curing agent for -OH and -COOH systems. Since the silanol (-CH3OH) produced by the hydrolysis of silica sol, methyltrimethoxysilane and methyltriethoxysilane, the film-forming substances of ceramic coatings, all have -OH, and the surface of hydroxyethyl cellulose molecules is also rich in -OH, the organic titanium crosslinking agent can react with the ceramic coating system to undergo a crosslinking reaction; the crosslinking reaction speed is related to the pH of the system. When the pH is higher than 5.2, the crosslinking speed is slow, resulting in insufficient primer thickness and poor wear resistance of the final coating; when the pH is lower than 4.0, the crosslinking speed is too fast, the paint film has poor leveling and low gloss.

[0089] Since the surface energy of the metal substrate is high, the surface is hydrophilic and there is a certain amount of -OH, the organic titanium crosslinker reacts with the -OH on the surface of the substrate to improve the adhesion between the paint film and the substrate.

[0090] The steps for preparing the clear topcoat are as follows:

[0091] (1) mixing an organic titanium crosslinking agent and isopropanol in a weight ratio of 1:1-1.5:1 and setting aside;

[0092] (2) Silane, formic acid, leveling agent, non-stick additive, emulsifier, deionized water, and remaining isopropanol were mixed evenly, and then silica sol was added. After rolling at 120-150 rpm for 12-14 hours, a ceramic topcoat was obtained, and the tested pH was 4.0-5.2.

[0093] The construction method of the topcoat is the same as that of the primer. The solution in step (1) should be mixed evenly with the topcoat before construction and then applied immediately. Otherwise, it needs to be stored separately.

[0094] The reaction process of ceramic coating is mainly divided into the following two steps: (1) siloxane is hydrolyzed under acidic conditions to generate silanol; (2) silica sol and silanol undergo condensation reaction to generate a cross-linked structure coating. -OH groups remain on the surface of the ceramic coating formed after the reaction. Since -OH groups are hydrophilic, the water resistance of the ceramic coating is slightly poor, which is reflected in the serious decrease in non-stickiness after boiling water. The organic titanium cross-linking agent added in the invention can undergo cross-linking reaction with -OH, so some or even all of the -OH groups remaining on the surface of the coating can be eliminated, greatly improving the water resistance and non-stickiness durability of the coating.

[0095] The above transparent ceramic coating can be applied to small kitchen appliances. The construction process is as follows:

[0096] Workpiece, sandblasting or shot blasting, nitriding, spraying transparent ceramic primer, spraying transparent ceramic topcoat, curing.

[0097] (1) The workpiece is a component for a small kitchen appliance, such as an air fryer basket, a microwave oven, an oven interior panel, etc.

[0098] (2) Sand blasting: Using compressed air as the power, use 60-80 mesh white corundum or brown corundum sand to spray at high speed onto the surface of the workpiece to be processed. After sand blasting, the surface roughness of the workpiece reaches 3-5μm.

[0099] Function: Make the surface of the workpiece obtain a certain degree of cleanliness and roughness, and increase the adhesion between the workpiece and the coating.

[0100] (3) Nitriding treatment process: The nitriding furnace heats the workpiece to 550-570°C, injects ammonia and nitrogen, controls the furnace pressure at 11-13 kPa, and the nitriding time is 2-3 hours. The workpiece is taken out after natural cooling.

[0101] Function: Improve the surface hardness, density and corrosion resistance of the workpiece. The surface of the workpiece is black-gray after nitriding.

[0102] (4) Spraying transparent primer: Spraying at room temperature, the primer wet film thickness is 15-20μm, the solid content of the transparent primer is about 40%, and the primer dry film thickness is about 6-8μm.

[0103] (5) Spraying transparent topcoat: After spraying the primer, spray the topcoat in a wet-on-wet manner. The wet film thickness of the topcoat is 20-30 μm. The solid content of the topcoat is about 40%, and the dry film thickness of the transparent topcoat is 8-12 μm.

[0104] (6) Curing: 80-100°C, 3-5 min; 200-260°C, 8-10 min, test performance after natural cooling.

[0105] Example 1

[0106] The present embodiment relates to a transparent ceramic coating, which is divided into two layers, a primer and a topcoat, both of which are colorless and transparent; wherein the primer is calculated as 100%, and the composition is shown in Table 1; the topcoat is calculated as 100%, and the composition is shown in Table 1.

[0107] The preparation of the transparent ceramic coating of this embodiment includes the preparation of a primer and the preparation of a topcoat. The preparation steps of the primer are as follows:

[0108] (1) Mix the organic titanium crosslinking agent and isopropyl alcohol in a weight ratio of 1:1 and set aside; store separately and record as primer composition 1.

[0109] (2) Preparation of 5 wt% hydroxyethyl cellulose aqueous solution: Weigh 95 g of deionized water and 5 g of hydroxyethyl cellulose. First, control the deionized water to be above 20° C. and gradually add hydroxyethyl cellulose under stirring until it becomes a uniform and transparent solution.

[0110] (3) Add the formulated amount of silica sol to the 5 wt % hydroxyethyl cellulose aqueous solution while stirring, mix well and set aside.

[0111] (4) Silane, formic acid, leveling agent, deionized water and the remaining isopropanol were mixed evenly, and then the solution of step (3) was added, and the mixture was placed on a roller stand and rolled at 135 rpm for 13 hours to obtain a transparent ceramic primer composition 2 with a pH of 4.8 and a coating viscosity of 13s for 4 cups.

[0112] The preparation steps of topcoat are as follows:

[0113] (1) Mix the organic titanium crosslinking agent and isopropyl alcohol in a weight ratio of 1:1 and set aside; store separately and record as topcoat composition 1.

[0114] (2) Silane, formic acid, leveling agent, non-stick agent, emulsifier, deionized water, and the remaining isopropyl alcohol were mixed evenly, and then silica sol was added. The mixture was placed on a roller stand and rolled at 135 rpm for 13 hours to obtain a ceramic topcoat composition 2. The tested pH was 4.5.

[0115] Example 2

[0116] This embodiment 2 relates to a transparent ceramic coating, which has a colorless and transparent primer and a topcoat; wherein the primer is calculated as 100%, and the composition is shown in Table 1; the topcoat is calculated as 100%, and the composition is shown in Table 1.

[0117] The preparation of the transparent ceramic coating is basically the same as in Example 1, except that:

[0118] In the preparation of the primer, (1) the organic titanium crosslinker and isopropanol were mixed uniformly in a weight ratio of 1.2:1 and set aside for use; and stored separately. (4) After rolling at 120 rpm for 14 hours, a transparent ceramic primer was obtained with a pH of 4.0 and a coating-4 cup viscosity of 15s.

[0119] In the preparation of the topcoat, (1) the organic titanium crosslinker and isopropanol are mixed evenly in a weight ratio of 1.2:1 and set aside for use; and stored separately. (2) Silane, formic acid, leveling agent, non-stick additive, emulsifier, deionized water, and the remaining isopropanol are mixed evenly, and then silica sol is added, placed on a roller frame, and rolled at 120 rpm for 14 hours to obtain a ceramic topcoat, and the tested pH is 4.2.

[0120] Example 3

[0121] This embodiment 3 relates to a transparent ceramic coating, which has a colorless and transparent primer and a topcoat; wherein the primer is calculated as 100%, and the composition is shown in Table 1; the topcoat is calculated as 100%, and the composition is shown in Table 1.

[0122] The preparation of the transparent ceramic coating is basically the same as in Example 1, except that:

[0123] In the preparation of the primer, (1) the organic titanium crosslinker and isopropanol are mixed uniformly in a weight ratio of 1.5:1 and set aside for use; and stored separately. (4) The primer is placed on a roller stand and rolled at 150 rpm for 12 hours to obtain a transparent ceramic primer having a pH of 5.2 and a coating-4 cup viscosity of 12s.

[0124] In the preparation of the topcoat, (1) the organic titanium crosslinker and isopropanol are mixed evenly in a weight ratio of 1.5:1 and set aside for use; and stored separately. (2) Silane, formic acid, leveling agent, non-stick additive, emulsifier, deionized water, and the remaining isopropanol are mixed evenly, and then silica sol is added, placed on a roller frame, and rolled at 150 rpm for 12 hours to obtain a ceramic topcoat, and the test pH is 5.0.

[0125] Example 4

[0126] This embodiment 4 relates to a transparent ceramic coating, which has a colorless and transparent primer and a topcoat; wherein the primer is calculated as 100%, and the composition is shown in Table 1; the topcoat is calculated as 100%, and the composition is shown in Table 1. The preparation of the transparent ceramic coating is basically the same as that of embodiment 1.

[0127] Example 5

[0128] This embodiment 5 relates to a transparent ceramic coating, which has a colorless and transparent primer and a topcoat; wherein the primer is calculated as 100%, and the composition is shown in Table 1; the topcoat is calculated as 100%, and the composition is shown in Table 1. The preparation of the transparent ceramic coating is basically the same as that of embodiment 1.

[0129] Comparative Examples 1 to 6

[0130] Comparative Examples 1 to 6 respectively relate to a transparent ceramic coating having a colorless and transparent primer and topcoat; wherein the primer is calculated as 100%, and the composition is shown in Table 1; the topcoat is calculated as 100%, and the composition is shown in Table 1. The preparation of the transparent ceramic coating is basically the same as Example 1.

[0131] Table 1 Coating composition and dosage of Examples and Comparative Examples (wt.%)

[0132]

[0133]

[0134] Example 6: Coating performance test

[0135] The coatings prepared in the above Examples 1-5 and Comparative Examples 1-6 were applied by the following method and then subjected to main performance tests. The application process is as follows:

[0136] (1) Sand blasting: Using compressed air as the power, use 60 mesh white corundum sand to spray at high speed onto the surface of the workpiece spatula to be processed. After sand blasting, the surface roughness of the workpiece reaches 4-5μm.

[0137] (2) Nitriding treatment process: The nitriding furnace heats the workpiece to 550°C, injects ammonia and nitrogen, controls the furnace pressure at 11 kPa, and the nitriding time is 2 hours. The workpiece is taken out after natural cooling.

[0138] (3) Spraying transparent primer: Mix primer composition 1 and primer composition 2 which are stored separately during primer preparation and apply them immediately. Spray at room temperature. The wet film thickness of the primer is 15 μm. The solid content of the transparent primer is about 40%, and the dry film thickness of the primer is about 6 μm.

[0139] (4) Spraying transparent topcoat: Mix topcoat composition 1 and topcoat composition 2 which are stored separately during the preparation of primer evenly and apply the mixture immediately. Specifically, after spraying the primer, spray the topcoat in a wet-on-wet manner. The wet film thickness of the topcoat is 20 μm. The solid content of the topcoat is about 40%, and the dry film thickness of the transparent topcoat is 8 μm.

[0140] (5) Curing: 80°C, 5 min; 200°C, 10 min, and test performance after natural cooling.

[0141] The workpieces of Examples 1-5 were black-gray after sandblasting and nitriding, and showed a color and appearance similar to that of fluorocarbon coatings after spraying with transparent ceramic coatings. Figure 1 The film thickness of the two layers of transparent ceramic coating is about 14 μm. This film thickness will not cause sagging when sprayed at room temperature, nor will it accumulate in the holes and gaps of the workpiece. The qualified rate of finished products is increased from 60% to more than 96%. The test items and test methods involved in the main performance tests of the coatings in the above embodiments and comparative examples are shown in Table 2:

[0142] Table 2. Main performance test items of coating

[0143]

[0144]

[0145] The test results are shown in Table 3 and Table 4:

[0146] Table 3

[0147]

[0148] Table 4

[0149]

[0150]

[0151] Application Examples

[0152] The coating prepared in Example 1 was applied to the air fryer basket using the following method, and the application process was as follows:

[0153] (1) Sand blasting: Using compressed air as the power, 80 mesh white corundum sand is sprayed at high speed onto the surface of the air fryer basket to be treated. After sand blasting, the surface roughness of the workpiece reaches 3-4μm.

[0154] (2) Nitriding treatment process: The workpiece is heated to 570°C in a nitriding furnace, ammonia and nitrogen are injected, the furnace pressure is controlled at 13 kPa, the nitriding time is 3 hours, and the air fryer basket is taken out after natural cooling.

[0155] (3) Spraying of transparent primer: Mix primer composition 1 and primer composition 2 which are stored separately during primer preparation and apply immediately after mixing evenly. Spray at room temperature.

[0156] (4) Spraying transparent topcoat: Mix the topcoat composition 1 and topcoat composition 2 which are stored separately during the preparation of the primer evenly and apply the mixture immediately. Specifically, after spraying the primer, spray the topcoat in a wet-on-wet manner.

[0157] (5) Curing: 100℃, 3min; 260℃, 8min, and then cool naturally. The coating gloss is 45, and the film thickness is 20μm. The air frying basket has an appearance similar to that of fluorine coating, with no coating dripping and accumulation in the pores and gaps, excellent non-stickiness, and qualified.

[0158] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A transparent ceramic coating, comprising a primer and a topcoat, both of which are colorless and transparent, wherein the primer, calculated as 100%, is composed of: silica sol: 42-45%, silane: 30-32%, 5wt% hydroxyethyl cellulose aqueous solution: 4-5%, formic acid: 0.7-1.0%, leveling agent: 0.5-1%, isopropyl alcohol: 8-10%, organic titanium crosslinking agent: 3-4%, and deionized water: the balance; The topcoat is composed of 100% silica sol: 36-38%, silane: 36-38%, formic acid: 0.7-1%, leveling agent: 1-1.5%, non-stick agent: 5-6%, emulsifier: 0.5-1%, isopropyl alcohol: 8-10%, organic titanium cross-linking agent: 1-2%, and deionized water: the balance.

2. The transparent ceramic coating according to claim 1, characterized in that: The transparent ceramic coating is used for the surface of the workpiece after sandblasting or shot blasting and nitriding treatment.

3. The transparent ceramic coating according to claim 1, characterized in that: The silane is a combination of methyltrimethoxysilane and methyltriethoxysilane in a mass ratio of 3:1 to 4:1; the organic titanium crosslinking agent is DuPont TM 371.

4. The transparent ceramic coating according to claim 1, characterized in that: In the topcoat or primer, the weight ratio of isopropyl alcohol to the organic titanium crosslinking agent is 1:1-1.5:1; And / or, the non-stick auxiliary agent is a non-stick auxiliary agent having a hydroxyl group at the end of the molecular chain; And / or, the emulsifier is a cationic emulsifier with an organic quaternary ammonium salt structure.

5. A method for applying the transparent ceramic coating in small kitchen appliances as claimed in claim 1, characterized in that: The method comprises the steps of sandblasting or shot blasting the workpiece, nitriding the workpiece, spraying a transparent ceramic primer, spraying a transparent ceramic topcoat and then curing the workpiece.

6. The application method according to claim 5, characterized in that After the workpiece is sandblasted or shot blasted, the surface roughness of the workpiece reaches 3-5 μm; And / or, the treatment temperature of the nitriding treatment is 550-570°C, the pressure of the nitriding furnace is controlled at 11-13kpa, and the nitriding time is 2-3hr; And / or, the curing process is: 80-100°C, 3-5 min; 200-260°C, 8-10 min.

7. The application method according to claim 5, characterized in that The spray transparent primer is prepared by mixing a primer composition 1 obtained by mixing an organic titanium crosslinking agent and isopropyl alcohol in a weight ratio of 1:1-1.5:1 with a primer composition 2 obtained by mixing the remaining compositions, and then spraying at room temperature, and the dry film thickness of the primer is 6-8 μm; The spraying transparent topcoat is constructed by mixing topcoat composition 1 obtained by mixing an organic titanium crosslinking agent and isopropyl alcohol in a weight ratio of 1:1-1.5:1 with topcoat composition 2 obtained by mixing other components. Specifically, after spraying the primer, the topcoat is sprayed in a wet-on-wet manner. After curing, the dry film thickness of the transparent topcoat is 8-12 μm.

8. The application method according to claim 5, characterized in that The workpiece includes an air fryer basket, a microwave oven, an interior panel of an oven, or a spatula.

9. A method for preparing a transparent ceramic coating as claimed in claim 1, characterized in that: The method comprises the following steps: A. Preparation of primer: A1. Mix the organic titanium crosslinking agent and isopropanol in a weight ratio of 1:1-1.5:1 and set aside, which is recorded as primer composition 1; A2, adding silica sol to 5wt% hydroxyethyl cellulose aqueous solution and mixing evenly; A3, silane, formic acid, leveling agent, deionized water, and the remaining isopropanol are mixed evenly, and then the solution of step A2 is added, and the mixture is placed on a roller frame, and rolled at 120-150 rpm for 12-14 hours to obtain a transparent ceramic primer composition 2; B. Preparation of topcoat: B1, mixing the organic titanium crosslinking agent and isopropyl alcohol in a weight ratio of 1:1-1.5:1, and setting aside for use, which is recorded as topcoat composition 1; B2. Evenly mix silane, formic acid, leveling agent, non-stick additive, emulsifier, deionized water and the remaining isopropanol, then add silica sol, place on a roller stand, roll at 120-150 rpm for 12-14 hours to obtain ceramic topcoat composition 2, and the tested pH is 4.0-5.

2.

10. The method for preparing the transparent ceramic coating according to claim 9, characterized in that: The transparent ceramic primer 2 has a pH of 4.0-5.2 and a viscosity of 12-15 seconds after coating with a 4-cup coating; the ceramic topcoat 2 has a pH of 4.0-5.2.

Citation Information

Patent Citations

  • Water-based porcelain film coating and preparation method thereof

    CN103725052A

  • Waterborne polyurethane waterproof coating and cold-method preparation process thereof

    CN114181607A

  • High-temperature-resistant long-acting non-stick ceramic coating and preparation method thereof

    CN115322598A

  • Ceramic coating for etching pot as well as preparation method and application of ceramic coating

    CN117384546A

  • Ceramic Coating Composition for Dissipating Heat and Method for Manufacturing the Same

    KR1020120025320A